Co-loading of finasteride and baicalin in phospholipid vesicles tailored for the treatment of hair disorders. Issue 30 (23rd July 2020) - Mir-Palomo, Silvia; Nácher, Amparo; Ofelia Vila-Busó, M. A.; Caddeo, Carla; Manca, Maria Letizia; Saurí, Amparo Ruiz; Escribano-Ferrer, Elvira; Manconi, Maria; Díez-Sales, Octavio
Abstract : A study of baicalin and/or finasteride nanovesicles for hair growth promotion. Abstract : Hair loss affects a large number of people worldwide and it has a negative impact on the quality of life. Despite the availability of different drugs for the treatment of hair disorders, therapeutic options are still limited and scarcely effective. An innovative strategy to improve the efficacy of alopecia treatment is presented in this work. Finasteride, the only oral synthetic drug approved by Unites States Federal Drug Administration, was loaded in phospholipid vesicles. In addition, baicalin was co-loaded as an adjuvant. Their effect on hair growth was evaluated in vitro and in vivo . Liposomes, hyalurosomes, glycerosomes and glycerol-hyalurosomes were manufactured by using a simple method that avoids the use of organic solvents. All the vesicles were small in size (∼100 nm), homogeneously dispersed (polydispersity index ≤0.27) and negatively charged (∼−16 mV). The formulations were able to stimulate the proliferation of human dermal papilla cells, which are widely used in hair physiology studies. The analysis of hair growth and hair follicles of C57BL/6 mice, treated with the formulations for 21 days, underlined the ability of the vesicles to improve hair growth by the simultaneous follicular delivery of finasteride and baicalin. Therefore, the developed nanosystems can represent a promising tool to ensure the efficacy of the local treatment of hair loss.